2003
DOI: 10.1021/ma021634o
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Poly(ethylene oxide) Segmental Dynamics in Blends with Poly(methyl methacrylate)

Abstract: Miscible blends of perdeuteriopoly(ethylene oxide) (d4PEO) and poly(methyl methacrylate) (PMMA) were studied using deuterium NMR over the concentration range of 0.5−30% d4PEO using 2−4 Larmor frequencies ranging from 31 to 76 MHz. Spin−lattice relaxation times and line widths were measured from 300 to 475 K. Over this range PEO is liquidlike or rubbery in terms of its dynamics even though many of the measurements are below the blend glass transition temperature. There is no indication of the DSC glass transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
266
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(294 citation statements)
references
References 37 publications
26
266
2
Order By: Relevance
“…9 This is not the case for the 10 wt % blend where PEO moves much slower than would be expected if the same composition dependence was continued. This could be due to labeling issues or an increasing contribution from the collective dynamics of deuterated PMMA.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…9 This is not the case for the 10 wt % blend where PEO moves much slower than would be expected if the same composition dependence was continued. This could be due to labeling issues or an increasing contribution from the collective dynamics of deuterated PMMA.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, NMR data show that the slow process is quite stretched, with values of 0.28. 9 At the spatial scale provided in the figure, values from QENS range between 0.35 and 0.40 at low temperature and increase to between 0.5 and 0.6 at the highest temperatures measured. Also shown in Figure 6 are times from a recent QENS study on PEO dynamics in this system.…”
Section: Characterization Of the Fast And Slow Processesmentioning
confidence: 93%
See 2 more Smart Citations
“…In particular, when different theories purport to explain the same phenomena, new experimental facts are crucial. The recent deuterium NMR study of blends of deuterated poly(ethylene oxide) (d 4 PEO) and poly-(methyl methacrylate) (PMMA) by Lutz et al 1 is such an example in the field of component dynamics of miscible polymer blends. The authors found that the segmental dynamics of d 4 PEO are nearly independent of composition for blends ranging from 0.5% to 30% d 4 -PEO, over the temperature range studied, and are about 12 orders of magnitude faster than the dynamics of PMMA for a 3% d 4 PEO blend near its glass transition temperature, T g .…”
Section: Introductionmentioning
confidence: 99%